2009
DOI: 10.1097/mpg.0b013e318180af4f
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine Pancreatic Function Testing in Patients With Cystic Fibrosis and Pancreatic Sufficiency: A Correlation Study

Abstract: In CF-PS, poor correlation was found between IRT, fecal elastase-1, and CFA, therefore neither fecal elastase-1 in the stool nor IRT in the serum reaches the sensitivity or the specificity of the fecal fat excretion. Thus, fecal fat excretion is required in patients with CF for evaluation of pancreatic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 18 publications
1
26
0
3
Order By: Relevance
“…On the other hand, we observed significant differences among the groups for enzyme supplementation (p = 0.01) and genotype (p = 0.048). As reported previously [17,18], we found a strong association between genotype and enzyme supplementation (p = 0.001). Thus, more than 90% of underweight subjects had severe mutation on both alleles as well as enzyme supplementation.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, we observed significant differences among the groups for enzyme supplementation (p = 0.01) and genotype (p = 0.048). As reported previously [17,18], we found a strong association between genotype and enzyme supplementation (p = 0.001). Thus, more than 90% of underweight subjects had severe mutation on both alleles as well as enzyme supplementation.…”
Section: Discussionsupporting
confidence: 83%
“…Cohen and colleagues [60] performed the FE-1 and 72-h fecal fat tests in patients with CF and found that children with FE-1 B 15 lg/g stool had significantly lower (p = 0.009) CFA than those with residual pancreatic activity (FE-1 [ 15 lg/g stool), leading the authors to suggest that FE-1 be used to test pancreatic status in all children with CF. Some studies have also shown good correlation of the FE-1 test with fecal fat testing in this patient population [25], while others have indicated that fecal fat excretion should always be performed in patients with CF for evaluation of pancreatic function [61].…”
Section: Diagnosis Of Pancreatic Exocrine Insufficiency In Patients Wmentioning
confidence: 97%
“…However, the study by Durie et al shows that IRT fails to determine pancreatic function in patients under 7 years old [10], whilst PI is frequently diagnosed in CF patients at the age of 3-36 months [11]. The gold standard for the assessment of fecal fat loses among indirect tests is the quantitative 72-hour fecal fat excretion test, although the procedure is labor-intensive [12]. To avoid tedious procedures, several simpler alternatives were developed including fecal fat microscopy [13] and acid steatocrit [14].…”
Section: Discussionmentioning
confidence: 95%